The relationships between blood lactate elimination and production rate with cyclists` aerobic and anaerobic performance during laboratory testing - Reinpold, K.; Rannama, I (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: The aim of this study was to examine the relationships between blood lactate elimination (BLA^J and production (VLama<) rate with cyclists` aerobic and anaerobic performance parameters during laboratory testing. Methods: During the preparation period (in January). 12 competitive U23 road cyclists (20.2±1.5 yrs" 183.6±7.5 cm. 77.2±7.7 kg. Vo2ma)( 70.5±4.6 ml/min/kg) performed cycling incremental test (step 3 min, increment 30 W) using cyclists` personal racing bikes mounted on the cycling ergometer Cyclus 2. until exhaustion. Blood lactate (BLA) levels were measured 60 seconds after the incremental test ended and in the end of every 5-minute period during a 20-minute active recovery which was performed at 100 W load. BLAelim rate was calculated as a slope of linear fit of the measured samples during recovery period. The power (P [W/kg]) and oxygen uptake (VO2max [ml/min/kg]) levels at maximal (VO2-P; VO2max), the fi rst (AeL-P; AeL-VO2) and second (AnL-P; AnL-VO2) ventilatory threshold levels were assessed using Cosmed PFT Ergo. All parameters were normalized with body mass. After 20-minute active recovery cyclists performed 30-second maximal sprint test at fi xed cadence of 110 rpm, to determine anaerobic power and capacity. VLamax rate was calculated as VLamax = (LamaxPost - LaPre) / (ttest-talac) Abbr. are as follows: LamaxPost = maximal post exercise BLA (max. value measured every minute until the fi rst drop of the BLA), LaPre = BLA before test (last sample from the 20-minute recovery period), ttest = test duration (29 s), talac = alactic time (5.5 s). BLAelim and VLamax ratio was calculated (EPratio). Descriptive statistics were computed for all variables expressed as a mean±SD. Pearson correlation was used to examine the relationships between BLAelim and VLamax with aerobic and anaerobic performance parameters. Signifi cance level was set at p<0.05. Results: Descriptive statistics: AnL-P - 4.4±0.3 W/kg; AnL-VO2 - 63.2±3.8 ml/min/kg; VO2-P - 5.1±0.3 W/kg; VO2max - 70.5±4.6 ml/min/kg. EPratio correlated with AnL-P (r = 0.64); AnL-VO2 (r = 0.63) and VO2-P (r = 0.79); VO2max (r = 0.68). As EPratio, BLAelim had similar but weaker relationships (r = 0.49; 0.57; 0.74; 0.64, respectively) with aerobic parameters. VLamax did not correlate with any aerobic nor anaerobic performance parameters. Conclusions: Lactate elimination rate and the ratio of lactate elimination and production are good indicators for predicting cyclists` aerobic performance in preparation period, before the racing season starts. Anaerobic power and capacity were not correlated with lactate production rate.